Monitoring report on integration 2022 - McGinnity, Frances; Emma, Quinn; James, Laurence; Murphy, Keire; Curristan, Sarah (ESRI and Department of Children, Equality, Disability, Integration and Youth, 2023)
Integration not only allows migrants to contribute to the economic, social, cultural and political life of their host country, but it is also important for social cohesion and inclusive growth. Keeping an ongoing record of differences in outcomes between the foreign-born and Irish-born population in these domains provides both policymakers and the general public with important information to assess integration outcomes and to respond to policy challenges. The 2022 Monitoring Report on Integration is the eighth in a series of published Monitoring Reports since 2011. Previous reports examined outcomes for Irish nationals and foreign nationals; in view of the increasing acquisition of Irish citizenship among migrants, this report distinguishes migrants based on their place of birth (Ireland or abroad). Like before, the report considers indicators proposed at the European Ministerial Conference on Integration held in Zaragoza in 2010 and examines how migrants compare to the Irish-born population in four key domains: employment, education, social inclusion and active citizenship (European Commission, 2010).